Constitutive Plasminogen Activator Inhibitor 1 (PAI-1) Biosynthesis in Human Hep G2 Hepatoma Cells Is Maintained by an Autocrine Factor - Bergonzelli, Gabriela E; Kruithof, Egbert K O (Thrombosis and Haemostasis, 1991)
We studied the production of PAI-1 by human Hep G2 hepatoma cells. When culturing these cells in fresh medium (FM), PAI-1 accumulation rate was not linear: PAI-1 antigen after 24 h was 200 ng/106 cells while in subsequent 24 h periods, it was on average 1,000 ng/106 cells. Culture of Hep G2 cells in regular changes of a 12 h conditioned medium (CM) obtained from other Hep G2, instead of in FM, resulted in a 2-fold higher PAI-1 accumulation. In cells incubated in FM, PAI-1 mRNA declined rapidly after medium change and returned to basal levels after 24 h. In contrast, PAI-1 mRNA remained relatively stable when CM was used. The acute phase mediator interleukin 6 (IL-6) was not responsible for the autocrine stimulation of PAI-1: neither IL-6 nor antibodies to IL-6 altered the observed variations in PAI-1 expression. Our studies suggest the presence of an unknown PAI-1 stimulating factor.